Randomised, double-blind, placebo-controlled study evaluating the effect of allopurinol on the risk of cardiovascular events in patients with high and very high cardiovascular risk, including the presence of long-COVID-19 syndrome: the ALL-VASCOR study protocol - Krzysztof Narkiewicz; Aleksander Prejbisz; Andrzej Januszewicz; Katarzyna Lewandowska; Dawid Lipski; Paweł Uruski; Jacek Wolf; Marek Rajzer; Andrzej Więcek; Andrzej Tykarski (BMJ Open)
Introduction Numerous studies, but not all, have suggested a positive effect of allopurinol on the cardiovascular system. The randomised, double-blind, placebo-controlled study evaluating the effect of allopurinol on the risk of cardiovascular events in patients with high and very high cardiovascular risk, including the presence of long-COVID-19 syndrome (ALL-VASCOR) study aims to evaluate the efficacy of allopurinol therapy for improving cardiovascular outcomes in patients at high and very high cardiovascular risk excluding ischaemic heart disease. This is particularly important due to the high cost of cardiovascular disease treatment and its status as one of the leading causes of mortality.Methods and analysis The ALL-VASCOR study is a randomised, double-blind, placebo-controlled, multicentre trial that examines the effect of allopurinol therapy (200–500 mg of allopurinol daily) versus an equivalent dose of placebo on the risk of cardiovascular events in 1116 patients aged 40–70 with serum uric acid levels above 5 mg/dL at high and very high risk of cardiovascular disease. The ALL-VASCOR study will also assess the occurrence of long-COVID-19 syndrome. The study will measure primary and secondary as well as additional endpoints and the planned intervention will end on 31 July 2028 unless advised otherwise by the Safe Monitoring Board or other applicable authorities. Participant recruitment is planned to begin in March 2024 in Poland.Ethics and dissemination The study was ethically approved by the Bioethics Committee of Poznan University of Medical Sciences (No 03/23, 12 January 2023). The results are expected after 2028 and will be disseminated in peer-reviewed journals and at international conferences.Protocol version number 01–15 November 2022.Trial registration number EudraCT: 2022-003573-32, 27 October 2022, ClinicalTrials: NCT05943821, 13 July 2023.